Pengaruh Kualitas Produk, Persepsi Harga Dan Promosi Penjualan Terhadap Keputusan Pembelian Mobil Suzuki Karimun Wagon R Di PT. Citra Asri Buana Cabang Nanggewer Bogor - Annisa Ussolikhah; Suadi Sapta Putra; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research aims to determine and analyze the effect of product quality, price perception and sales promotion on purchasing decisions for Suzuki Karimun Wagon R at PT. Citra Asri Buana, Nanggewer Bogor branch. The research method used in this research is descriptive quantitative with the population in the study of consumers of Suzuki Karimun Wagon R cars. There are 4 (four) variables studied in this study, namely product quality (X1), price perception (X2), sales promotion (X3). and purchasing decisions (Y). The sample used in this study were 100 respondents. The technique used in this research is purposive sampling, namely taking a sample considering certain criteria. By using purposive sampling, it is hoped that the sample will meet the criteria needed in this study, so that the sample answers become more objective. This research data uses primary data by distributing questionnaires with multiple linear regression method which is processed using SPSS 25. The results based on multiple linear regression analysis show that product quality, price perception and sales promotion have a positive and significant effect on purchasing decisions. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Keywords: Product Quality, Price Perception, Sales Promotion and Purchase Decision.